Commercialization Presentation of Rumah Ketam UNIMAS (RKU) Upgraded, Research and Innovation Done in Sarawak for Commercialization - Saiful Bahari, Hj Mohd Yusoff; Ibrahim, Zalina (2018)
Sarawak International Business Exhibition and Conference (SIBEC) 2018. Commercialization Presentation of Rumah Ketam UNIMAS (RKU) Upgraded, Research and Innovation Done in Sarawak for Commercialization. Presentation to other universities, and potential investors.